Investigation of rhizobial dehalogenase control system in dehalogenase gene expression - Huyop, Fahrul Zaman; Abdul Manan, Fazilah; Hussin, Huszalina (Faculty of Sciences, 2009)
The DNA sequence upstream of dehE gene encoding dehalogenase E (DehE) of Rhizobium sp. RC1 was determined and contained an open reading frame, designated dehR, which encoded a protein with a significant similarity to dehalogenase regulatory protein (DehR). Plasmid DNA designated pFH648 that carry both dehE and dehR genes were cloned from Rhizobium sp. RC1 genomic DNA. Rhizobium sp. RC1 genetic organization was determined, suggesting dehE was controlled by the product of dehR. Current study proved previous analysis by growth experiment, E.coli XL10 Gold::pFH648 (dehE+, dehR+) has the ability to grow in minimal media supplied with 20 mM D,L-2CP as sole source of carbon. Whereas, E.coli XL10::pSC520 (dehE+) lacking dehR gene and E.coli XL10 Gold::pFH45 (dehR+) lacking dehE gene did not grow in minimal media supplied with 20 mM D,L-2CP as sole source of carbon and energy, suggesting both dehE and dehR genes were needed to allow growth in D,L-2CP minimal media. Since both dehE and dehR were neighboring genes with opposite direction of transcription, promoters of dehE, “24 (TGGCA)/“12 (TTGCTA) and dehR, -10 (ACCA)/-35 (AGGT) were identified by sequence homology. Gel shift experiment supported the proposed genetic organisation and regulation for the Rhizobium sp. RC1 dehalogenase gene.